Use of stem cells in plastic surgery: An integrative literature review (Research, Society and Development, 2023)
This article proposes a discussion about the perspectives of the use of stem cells in plastic surgery, through a very detailed literature review. Stem cells (SC) are characterized by being undifferentiated or unspecialized, having the ability to self-renew and differentiate into various cell types (multilineage), from the same tissue and from different tissues with different functions. In view of the studies analyzed, we understand that stem cells derived from adipose tissue are an advance in plastic surgery, as they are capable of differentiating into various other tissues, being very efficient in aesthetic and reparative surgeries. It was found that when grafted, they also promote angiogenesis, accelerating the healing process and increasing the success rate of the procedure. Furthermore, as it is an autologous transplant, it presents a low risk of rejection and disease transmission compared to possible sources of exogenous stem cells. However, it was discussed by several professionals in the field about the importance of using this technique by trained professionals, demonstrating the need for study and knowledge of the technique by plastic surgeons, so that confidence and success in the procedure can be established.